Chinese Patent Medicines in the Treatment of Coronavirus Disease 2019 (COVID-19) in China - Zhuang, Wei; Fan, Zheng; Chu, Yanqi; Wang, Haizheng; Yang, Ying; Wu, Li; Sun, Nan; Sun, Ge; Shen, Yuqiao; Lin, Xiaolan; Guo, Guiming; Xi, Shengyan (Frontiers in Pharmacology, 2020)
Coronavirus Disease 2019 (COVID-19) is an emerging, rapidly evolving disease, with no recommended effective anti-coronavirus drug treatment. Chinese Patent Medicines (CPMs) have, however, been widely used to treat COVID-19 in China, and a number of clinical practice results have shown them to have a significant role in its treatment. Consequently, numerous guidelines and expert consensus have recommended the use of CPMs to treat COVID-19. In order to provide up-to-date information on the pharmacology and clinical research on CPMs in the treatment of COVID-19, discuss the research findings, and to better guide clinical application and scientific research on CPMs in the treatment of COVID-19, the frequencies of CPM recommendations by guidelines and expert consensus for treatment of COVID-19 in China were ranked. This report identifies the top 10 CPMs, which include Huoxiang Zhengqi capsule (HXZQC), Lianhua Qingwen capsule (LHQWC), Jinhua Qinggan granule (JHQGG), Shufeng Jiedu capsule (SFJDC), Tanreqing injection (TRQI), Xiyanping injection (XYPI), Xuebijing injection (XBJI), Shenfu injection (SFI), Shengmai injection (SMI) and Angong Niuhuang pill (AGNHP). Relevant studies from 2000 to 2020 on these top 10 CPMs, covering usage, dosage, mechanism, curative effect and precautions, were collected from pharmacopoeia, reports and theses via library and digital databases (including PubMed, CNKI, Google Scholar, Web of Science and Elsevier). The properties of the top 10 CPMs included antiviral, antibacterial, anti-inflammatory, antipyretic and analgesic, anti-acute lung injury, anti-shock, immune regulation, and enhancement of pulmonary function. In addition, clinical research results and Chinese treatment data showed that the CPMs had good therapeutic efficacy in the treatment of COVID-19, and adverse reactions were minimal. So, clearly-knowing the characteristics and precautions of the top 10 CPMs may help clinicians to use rationally, improve therapeutic efficacy, and promote the role of Chinese Medicine in global epidemic prevention for COVID-19.